2010
DOI: 10.1089/ten.tea.2009.0589
|View full text |Cite
|
Sign up to set email alerts
|

Viable Fibroblast Matrix Patch Induces Angiogenesis and Increases Myocardial Blood Flow in Heart Failure After Myocardial Infarction

Abstract: The 3DFC functions as a cell delivery device providing matrix support for resident cell survival and integration into the heart. The imbedded fibroblasts of the 3DFC release a complex blend of cardioactive cytokines promoting increases in microvessel density and anterior wall blood flow but does not improve ejection fraction or alter LV remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 45 publications
2
41
0
Order By: Relevance
“…Recent research has also shown the potential benefit of delivering fibroblasts to the infarct region. 27,28 Fibroblasts comprise about 70% of the total cells present in the heart. 29 They secrete the ECM and a number of growth factors, in particular vascular endothelial growth factor (VEGF), 28,29 which has a key role in the promotion of angiogenesis, 30,31 and acts as a mitogen, survival factor, and chemoattractant for endothelial cells (ECs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has also shown the potential benefit of delivering fibroblasts to the infarct region. 27,28 Fibroblasts comprise about 70% of the total cells present in the heart. 29 They secrete the ECM and a number of growth factors, in particular vascular endothelial growth factor (VEGF), 28,29 which has a key role in the promotion of angiogenesis, 30,31 and acts as a mitogen, survival factor, and chemoattractant for endothelial cells (ECs).…”
Section: Introductionmentioning
confidence: 99%
“…In rats, it was shown to improve myocardial blood flow to the infarcted region and shown to improve LV remodeling and function. 40 Additionally, this product has been shown to be effective in the treatment of chronically ischemic canine 43 and rat 27 hearts, resulting from MI. The beneficial effects of the product have been attributed to the sustained localized expression of VEGF and other angiogenic factors by the fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Heart failure is created in rats with the use of standard techniques developed in our laboratory. 23 In brief, Sprague-Dawley rats were infarcted by permanent ligature placement around the proximal left coronary artery. Rats undergoing this procedure develop large MIs as confirmed by LV end-diastolic pressure >16 mm Hg and the presence of a transmural scar.…”
Section: Methodsmentioning
confidence: 99%
“…23,24 In brief, hearts were arrested with potassium chloride and a catheter inserted into the LV via the aortic root. One end of the double-lumen LV catheter was connected to a volume infusion pump (Harvard Apparatus) and the other end to a pressure transducer zeroed at the level of the heart.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation